Covalent Organic Framework (COF) Derived Ni‐N‐C Catalysts for Electrochemical CO2 Reduction: Unraveling Fundamental Kinetic and Structural Parameters of the Active Sites. Issue 15 (16th February 2022) - Li, Changxia; Ju, Wen; Vijay, Sudarshan; Timoshenko, Janis; Mou, Kaiwen; Cullen, David A.; Yang, Jin; Wang, Xingli; Pachfule, Pradip; Brückner, Sven; Jeon, Hyo Sang; Haase, Felix T.; et al.
Abstract: Electrochemical CO2 reduction is a potential approach to convert CO2 into valuable chemicals using electricity as feedstock. Abundant and affordable catalyst materials are needed to upscale this process in a sustainable manner. Nickel‐nitrogen‐doped carbon (Ni‐N‐C) is an efficient catalyst for CO2 reduction to CO, and the single‐site Ni−N x motif is believed to be the active site. However, critical metrics for its catalytic activity, such as active site density and intrinsic turnover frequency, so far lack systematic discussion. In this work, we prepared a set of covalent organic framework (COF)‐derived Ni‐N‐C catalysts, for which the Ni−N x content could be adjusted by the pyrolysis temperature. The combination of high‐angle annular dark‐field scanning transmission electron microscopy and extended X‐ray absorption fine structure evidenced the presence of Ni single‐sites, and quantitative X‐ray photoemission addressed the relation between active site density and turnover frequency. Abstract : Nickel–nitrogen‐doped carbon (Ni‐N‐C) is an efficient catalyst for electrochemical CO2 reduction to CO, yet methods to evaluate the number of active Ni sites on the surface and turnover frequency remained elusive. Herein, a set of COF‐derived Ni‐N‐C candidates is synthesized and a comprehensive analysis is undertaken to quantify the active Ni sites, addressing the relation between synthesis parameters, apparent reactivity, active site density, and turnover frequency.